Cryptococcus neoformans blood stream infection in severe COVID-19 pneumonia - Rama. V Thyagarajan; Kristin E. Mondy; Dusten T. Rose (IDCases, 2021)
Severe coronavirus disease (COVID-19) associated pneumonia leads to acute respiratory distress syndrome and emerging data suggest fungal coinfections also contribute to mortality in this patient population. Aspergillus ventilator associated pneumonia is increasingly recognized. We describe a case of likely reactivation of community acquired Cryptococcus neoformans in a patient with severe COVID-19.